Development of Quick Response Code (QR CODE) as A Plant Identification Innovation for SMA Muhammadiyah 1 Pontianak Students - Suhana Rosa; Mahwar Qurbaniah; Ari Sunandar (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2024)
QR code is a system that uses two-dimensional image codes which also originate from the evolution of barcodes. QR codes can be used as learning resources. This research aims to produce appropriate QR code learning media that get positive responses from students. The development of the QR code media uses the Research and Development method. In the 4-D development research model (Four D model), researchers only use up to 3 steps, namely: Define stage (Planning), Design stage (Designing) and Develop stage (Development). The research results show that the QR code media developed using expert validation sheets and response questionnaires received a score for the media aspect of 80.00% (feasible), the material aspect of 88.00% (very feasible), and the language aspect of 82.00% (very feasible). Meanwhile, the results of student responses used 2 development trials, these are small-scale trials 90% (very positive) and large-scale trials 88.41% (very positive). It can be concluded that the media developed in this research is valid and gets a very positive response from students.